Perencanaan Sistem Pemompaan pada Penambangan Timah Primer Shaft Lacat 4 Pt Menara Cipta Mulia Kelapa Kampit Belitung Timur - Aryuni Yusra Hamid; Delita Ega Andini; Haslen Oktarianty (MINERAL, 2021)
This research was conducted to redesign the pumping system in the air drying process within a maximum of 25 days. The method used is descriptive and quantitative methods with actual data in the form of pressure and suction pipe elevation, pipe length and diameter, catchment area, actual discharge and pump head, location coordinates.The runoff discharge is 1.89 m3 / s, is prevented from entering the mine area by creating a channel with discharge flow of 2.12 m3 / s. The total volume on Shaft Lacat 4 is 34,591.7 m3 . The pump at a depth of 20 m has a discharge of 229.37 m 3 / hour, while a depth of 28 m has a discharge of 210.73 m3 / hour. Assuming the ground water is 200.64 m3 / hour, the addition of one pump with a discharge of 36 m3 / hour so that the drying time for 24 days is 11.8 hours. Production is stacking the sump of 1 x 1 x 1.5 m, making a channel with dimensions of 10 cm x 10 cm.